PREDICTION OF PHYSICAL VARIABLE TO SQUAT LONG JUMP ACHIEVEMENT (A MULTIVARIATE CORRELATIONAL STUDY ON TRAINED STUDENTS OF A STATE SENIOR HIGH SCHOOL IN PEKALONGAN REGENCY) - Abdurrachman, Abdurachman; Sugiyanto, Sugiyanto; Doewes, Muchsin (UPI Press, 2018)
Achievement of squat long jump needs to be supported with several components that are divided into anthropometric elements and physical abilities. This study aims to determine the relationship and the extent to which squat long jump achievement can predict limb length, body mass index, body flexibility, and running speed. The subjects of this research were trained students of state senior high schools in Pekalongan Regency, with a total sample of 60 students. The independent variables in this research included limb length, body mass index, body flexibility, and running speed, whereas the dependent variables consisted of long jump and squat style achievement. The data were obtained through the test and measurement of each variable. This study used multivariate correlational method. Data were analyzed with normality test, linearity test, simple and multiple regression analysis, and hypotheses were tested with t-test and F-test. The results showed that limb length, body mass index, and flexibility had a positive relationship, whereas body mass index and running speed had a negative relationship with the squat long jump achievement. The prediction value of limb length was 0.027, body mass index -0.049, body flexibility 0.026, and running speed -0.234. The conclusion of this study is that there was a significant relationship among the variables, and limb length, body mass index, body flexibility and running speed can be predicted based on squat long jump achievement.